2021
DOI: 10.1111/jcpe.13553
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence and progression of periodontitis and methods of management in long‐term care: A systematic review and meta‐analysis

Abstract: Aim To systematically review the literature to evaluate the recurrence of disease of people in long‐term supportive periodontal care (SPC), previously treated for periodontitis, and determine the effect of different methods of managing recurrence. The review focused on stage IV periodontitis. Materials and methods An electronic search was conducted (until May 2020) for prospective clinical trials. Tooth loss was the primary outcome. Results Twenty‐four publications were retrieved to address recurrence of disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 63 publications
1
31
3
Order By: Relevance
“…For this guideline, a total of 13 systematic reviews (SRs) were conducted to support the guideline development process (Carra et al, 2021; Dommisch et al, 2021; Donos et al, 2021; Gennai et al, 2021; Gotfredsen et al, 2021; Kloukos et al, 2021; Leow et al, 2021; Martín et al, 2021; Montero et al, 2021; Orlandi et al, 2021; Papageorgiou et al, 2021; Ramanauskaite et al, 2021; Tomasi et al, 2021). The corresponding manuscripts are published within this special issue of the Journal of Clinical Periodontology.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For this guideline, a total of 13 systematic reviews (SRs) were conducted to support the guideline development process (Carra et al, 2021; Dommisch et al, 2021; Donos et al, 2021; Gennai et al, 2021; Gotfredsen et al, 2021; Kloukos et al, 2021; Leow et al, 2021; Martín et al, 2021; Montero et al, 2021; Orlandi et al, 2021; Papageorgiou et al, 2021; Ramanauskaite et al, 2021; Tomasi et al, 2021). The corresponding manuscripts are published within this special issue of the Journal of Clinical Periodontology.…”
Section: Methodsmentioning
confidence: 99%
“…The systematic review (Leow et al, 2021) assessed the role of professionally administered supportive periodontal care (SPC) in preventing tooth loss, periodontitis progression (clinical attachment loss, CAL) and associated health outcomes in patients with periodontitis who had completed active periodontal treatment.…”
Section: Long‐term Outcomes Of Treatment In Stage IV Periodontitis Pa...mentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review concluded that a small proportion of patients with stage III/IV periodontitis experience tooth loss during supportive periodontal care (SPC) (Leow et al, 2021). Assigning prognosis can be an effective tool for more predictable long‐term planning and management of a patient, particularly in the context of life‐long SPC as the fourth step of periodontal therapy (Sanz et al, 2020).…”
Section: Introductionmentioning
confidence: 99%